Neuronal guidance factor Sema3A inhibits neurite ingrowth and prevents chondrocyte hypertrophy in the degeneration of knee cartilage in mice, monkeys and humans - Shishu Huang; Dashuang Gao; Zhenxia Li; Hongchen He; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Jiancheng Zeng; Xiaojun Shi; Qinshen Hu; Yong Nie; et al. (Bone Research)
Abstract Osteoarthritis (OA) is a degenerative joint disease accompanied with the loss of cartilage and consequent nociceptive symptoms. Normal articular cartilage maintains at aneural state. Neuron guidance factor Semaphorin 3A (Sema3A) is a membrane-associated secreted protein with chemorepulsive properties for axons. However, the role of Sema3A in articular cartilage is still not clear. In the present studies, we investigated the functions of Sema3A in OA development in mice, non-human primates, and patients with OA. Sema3A has a protective effect on cartilage degradation, validated by the organoid culture in vitro and confirmed in chondrocyte-specific Sema3A conditional knockout mice. We demonstrated that Sema3A is a key molecule in maintaining cartilage homeostasis from chondrocyte hypertrophy via activating the PI3K pathway. The potential usage of Sema3A for OA treatment was validated in mouse and Rhesus macaque OA models through intra-articular injection of Sema3A, and also in patients by administering Sema3A containing platelet-rich plasma into the knee joints. Our studies demonstrated that Sema3A exerts a critical role in inhibiting neurite ingrowth and preventing chondrocyte hypertrophy in cartilage, and could be potentially used for OA treatment.